Effects of modified tall oil, chromium nicotinate, and L-carnitine on growth performance and carcass characteristics of growing-finishing gilts - O'Quinn, P.R.; Waylan, A.T.; Woodworth, J.C.; Owen, K.Q.; Goodband, Robert D.; Unruh, John A.; Nelssen, Jim L.; Tokach, Michael D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A trial was conducted to investigate the interactive effects of modified tall oil (MTO), chromium nicotinate (CrNic), and L-carnitine on growth performance and carcass characteristics of finishing gilts. For the overall trial, MTO increased ADG and ADFI, and CrNic improved F/G. A CrNic x MTO interaction occurred for belly firmness; feeding CrNic in diets without MTO improved firmness, but feeding it in diets with MTO decreased firmness. Feeding L-carnitine did not have any beneficial effects on either growth performance or carcass characteristics. The results of this trial indicate that either CrNic or MTO will improve growth performance with minimal effects on carcass characteristics.
Keywords: Swine; Modified tall oil; Chromium nicotinate; L-carnitine; Gilts